PROSES PERTUMBUHAN DAN HASIL DUA VARIETAS TANAMAN KEDELAI (Glycine max (L.) Merrill) DENGAN PERLAKUAN TIGA TIPE JARAK TANAM: Kata kunci: Jarak tanam, varietas, kedelai, pertumbuhan, hasil - Afringga Rohmawan; Siswadi Siswadi; Sumarmi Sumarmi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2023)
Research on the study of plant spacing on the growth and yield of two varieties of osoybean plants was carried out in May–July o2022, at the Tohudan Food Crops and Horticultural Seed Garden, Karanganyar. This study aims: to determine the effect f spacing on the growth and yield of two varieties of soybean plants. This study used a Completely Randomized Block Design (RAKL) which was arranged in a factorial manner with 2 treatment factors, namely spacing (J) and variety (V) which produced 6 combinations. J1: 20 cm x 20 cm spacing, J2: 20 cm x 30 cm spacing, J3: o20 cm x 40 ocm spacing, oV1: Anjasmoro ovariety, V2: Biosoy variety. Observations were made in the treatment plot. To find out whether there was an oeffect of spacing treatment on two varieties of soybean plants, then the observed data were analyzed using analysis of variance. Meanwhile, to find out the significance of the treatment, the BNJ test was used at the 5% level. The results showed (1) the height of soybean plantof the Anjasmoro variety othe ospacing oof othe onon-Anjasmoro variety range from o105,3 cm to 108,5. Affet plant height on Anjasmoro variety. The height variety Biosoy variety ranged from 81,67 – 92,25 cm. (2) Stem diameter of soybean varieties Anjasmoro and oBiosoy oranged ofrom o8,09 o– o8,92 omm, spacing was not significantly different for all treatments. (3) oThe number of pods per plant on the Anjasmoro variety with a spacing of 20 cm x 40 cm (J3) reached 134,25 pods, the heighest compared to other treatments. (4) The weight oof 100 soybean seeds of the Biosoy ovariety showed a yield of 22.37 – 23.56 grams which was better than the Anjasmoro variety, ranging from 15.63 – 16.07 grams